Blockchain systems and applications: evaluating the opportunities of the blockchain technology in various industries - Amin, Mohd Rushidi Mohd; Abbas, Mohd Saleh; Ismail, Albert Feisal; Rahmat, Robaisya; Zolkefle, Nor Zuleikha Nawal; Nordin, Mohd Norazmi (2023)
Blockchain technology is now viewed by many companies and industry communities as a technological solution and an active area of research. Blockchain can provide new chances and advantages to enterprises through greater efficiency, decreased costs, higher integrity and transparency, improved security, and enhanced traceability due to its decentralised and trustworthy nature. increase. While we see the majority of blockchain applications in the financial and banking industry, we are increasingly seeing experimentations and projected applications in other industries. In this white paper, a description of blockchain technology is given. It enumerates all the essential features, design components, and advantages that make blockchain a fantastic and distinctive technology. We also go through a taxonomy of blockchain systems and the most popular consensus protocols. This whitepaper also explores blockchain-based applications in various industries, namely finance, insurance, supply& chain management, energy, media & advertising, real estate, and medical sector. We will analyze the key issues facing the sector as well as blockchain based solutions and their implementation. The study identifies three major drawbacks of blockchain technology: scalability, security, and regulation, and portrays howsuch issues affect the use and adoption of blockchain technology.